STUDI LITERATUR KETERGANTUNGAN EMOSIONAL MAHASISWA FATHERLESS - Pangesti, Lia Nanik; Handayani, Arri; Ajie, Gregorius Rohastono (Universitas PGRI Semarang, 2024)
Fenomena fatherless atau ketidakhadiran sosok ayah dalam kehidupan anak menjadi isu yang semakin menonjol di Indonesia. Mahasiswa yang tumbuh dalam kondisi fatherless sering kali mengalami tantangan psikologis yang kompleks, salah satunya berupa ketergantungan emosional. Studi literatur ini bertujuan untuk mengkaji keterkaitan antara kondisi fatherless dengan kecenderungan ketergantungan emosional pada mahasiswa. Melalui telaah pustaka dari berbagai sumber nasional dan internasional, ditemukan bahwa ketidakhadiran ayah dalam masa perkembangan individu berdampak pada pembentukan regulasi emosi, harga diri, dan kemampuan menjalin relasi sosial. Ketergantungan emosional pada mahasiswa fatherless dapat muncul dalam bentuk kebutuhan akan validasi, rasa aman, serta kesulitan mengambil keputusan secara mandiri. Temuan ini mempertegas pentingnya pemahaman terhadap aspek emosional mahasiswa yang mengalami fatherlessness sebagai landasan dalam perancangan intervensi psikososial dan layanan bimbingan di perguruan tinggi.Kata kunci: fatherless; ketergantungan emosional; mahasiswa; perkembangan psikologis; studi literaturThe phenomenon of fatherlessness, or the absence of a father figure in a child's life, has become an increasingly prominent issue in Indonesia. Students who grow up in fatherless conditions often experience complex psychological challenges, one of which is emotional dependence. This literature review aims to examine the relationship between fatherlessness and the tendency toward emotional dependence in students. Through a review of various national and international sources, it was found that the absence of a father during an individual's developmental period impacts the formation of emotional regulation, self-esteem, and the ability to establish social relationships. Emotional dependency in fatherless students may manifest as a need for validation, a sense of security, and difficulty making decisions independently. These findings emphasize the importance of understanding the emotional aspects of students experiencing fatherlessness as a foundation for designing psychosocial interventions and counseling services in higher education institutions. Keywords: fatherlessness; emotional dependency; students; psychological development; literature review